KONSERVATISME ISLAM DAN INTOLERANSI KEAGAMAAN DI TASIKMALAYA - Amin Mudzakkir (Harmoni, 2017)
This paper observes Islamic conservatism and religious intolerance in Tasikmalaya. Based on historical analysis on the development and existence of Islam in Tasikmalaya, this paper looks at the symptoms of Islamic conservatism growing up at the end of 1990s which severely affected to the existence of Ahmadi and Shi‘i as minority groups. Mainly relying on deep interviews with local actors, this paper argues that intolerance towards religious minority has been facilitated by the policy of the state which tends to give privilege to majority groups.